Biogeochemical properties of water samples collected from Kevo, Utsjoki region in Finland during June 2023 - Tuomela, Nea; Elovaara, Samu; Kaartokallio, Hermanni; Hultman, Jenni; Thomas, David N (In: Tuomela, N et al. (2025): Dissolved organic matter properties and processing in a small arctic catchment with peatland and palsa features [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.981156, 2025)
This table contains biogeochemical properties collected from small ponds, headwaters and river in June 2023. Measurements include nutrient concentrations, dissolved organic carbon concentrations, optical propertied of dissolved organic matter, bacterial numbers and in-situ measurements.
Keywords: Arctic; Bacteria; biogeochemistry; CDOM; Palsa; Peatland; river